Trends in Teaching Civics with Learning Media: A Systematic Review - Damanhuri, Damanhuri; Ruhiat, Yayat; Nulhakim, Lukman; Ibidoja, Olayemi Joshua (FKIP Universitas Lampung, 2024)
Trends in Teaching Civics with Learning Media: A Systematic Review. Objectives: This systematic review evaluates the effectiveness of digital media-based learning media in Civics education. The study synthesizes existing literature to identify key trends, methodologies, and outcomes in the use of learning media for teaching civics. The review highlights the significant impact of the digital revolution on educational practices, particularly in enhancing student engagement and interactivity in Civics education. Method: The research utilizes a systematic review ensuring a comprehensive analysis of the impact and implementation of digital learning media in teaching civics. Key themes identified include experiential learning, problem-solving, civic engagement, reasoning, and civic literacy. Findings: Reveal a predominant focus on interactive media and video, reflecting a trend towards more engaging and immersive learning experiences. However, challenges such as the digital divide and the need for continuous teacher training are also discussed. The review underscores the importance of innovative approaches in civics education, with implications for curriculum development and pedagogical practices. Conclusion: Educators can foster a more informed and engaged learning environment by integrating digital media effectively and more curiously. The study concludes that while significant advances have been made, ongoing efforts are needed to address existing challenges and maximize the benefits of digital learning media in Civics education. Benchmarking these efforts against experiential learning, problem-solving, civic engagement, reasoning, and civic literacy must be applied with interactive learning approaches. Keywords: teaching civic, learning media, civic education, systematic review.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202472